Search
Ask a question
0 0

show how you arrives at the answer simplify completely 2[4(x+y) - 3(6x-15y)]

Please show the work all the way to the very answer if like terms then show the work to the very end.. thanks
Tutors, please sign in to answer this question.

1 Answer

2[4(x+y) - 3(6x-15y)]
 
The order of operations --> PEMDAS
 
P = operations within Parentheses
E = Exponents
M = Multiplication
D = Division
A = Addition
S = Subtraction
 
First distribute the 4 across the (x+y) and the 3 across the (6x - 15y)
 
2[4x + 4y -18x + 45y]
 
Next do the addition and subtraction of like terms within the brackets [ ]
 
2[4x - 18x + 45y + 4y]
 
2[-14x + 49y]
 
Finally, distribute (multiply) the 2 across the terms inside the bracket and you'll have your answer.